Surgical Treatment in Patients with Toxic Phosphorus Osteonecrosis of Facial Skull Middle Zone - Davit H. Ispiryan; Gagik Hakobyan; Anastasia Li; Ekaterina Yu. Diachkova; Yuriy Vasil'ev; Artur Kheygetyan; Elena Ivanova; Kirill Zhandarov; Natalia Kireeva; Roman Safronov; Alexey Serikov; Yuri A. Medvedev (MDPI AG, 2023)
During the last few years, in the territory of the Russian Federation, the number of cases of toxic phosphoric osteonecrosis of the jaws has increased against the background of taking drugs of "artisanal" production (pervitin, desomorphin). The aim of our study was to increase the effectiveness of surgical treatment of patients with a diagnosis of toxic phosphorus necrosis of the maxilla. We performed a comprehensive treatment of patients with a history of drug addiction and the above diagnosis. Surgical intervention in the volume of complete resection of pathologically altered tissues and reconstructive techniques using local tissues and a replaced flap made it possible to achieve good aesthetic and functional results in the early and late postoperative period. Thus, our proposed method of surgical treatment can be used in similar clinical situations.